Reasonably Traditional: Self–Contradiction and Self–Reference in Alasdair MacIntyre’s Account of Tradition–Based Rationality - Lott, Micah (Journal of religious ethics, 2002)
Alasdair MacIntyre’s account of tradition–based rationality has been the subject of much discussion, as well as the object of some recent charges of inconsistency. The author considers arguments by Jennifer Herdt, Peter Mehl, and John Haldane which attempt to show that MacIntyre’s account of rationality is, in some way, inconsistent. It is argued that the various charges of inconsistency brought against MacIntyre by these critics can be understood as variations on two general types of criticism: (1) that MacIntyre’s account of tradition–based rationality presents a picture of rationality with inconsistent internal elements, and (2) that MacIntyre, in the act of presenting his picture of rationality, makes the sort of claims to which his own account of rationality denies legitimacy, and thus MacIntyre’s account is self–referentially incoherent. In response to criticisms of the first sort, it is argued that MacIntyre can further clarify or develop his position to take the current criticisms into account without altering the fundamental aspects of his picture of rationality. In response to the charge of self–referential incoherence, it is argued that the charge rests on a mistaken understanding of MacIntyre’s position and of the nature of justification. In dealing with these arguments, the author hopes to not only vindicate MacIntyre’s account of rationality against the charges of some of its recent critics, but also to shed some light on the nature of arguments both for and against relativism and historicism.